Laparoscopic splenectomy and subsequent oncologic gastric surgery in cirrhotic patients with portal hypertension and hypersplenism - Zhan, Xiaoli; Chen, Yan; Wang, Yuedong (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Zhan X, Chen Y, Wang Y. Laparoscopic splenectomy and subsequent oncologic gastric surgery in cirrhotic patients with portal hypertension and hypersplenism. Turk J Gastroenterol 2018; 29: 130-1.